A Simple Approach to Isolate Slow and Fast Cycling Organic Carbon Fractions in Central European Soils—Importance of Dispersion Method - Just, Christopher; Poeplau, Christopher; Don, Axel; van Wesemael, Bas; Kögel-Knabner, Ingrid; Wiesmeier, Martin (Frontiers in Soil Science, 2021)
Numerous approaches were developed to isolate fast and slow cycling soil organic carbon (SOC) pools via physical and chemical fractionation. Most of these methods are complex, expensive and time consuming and therefore unsuited for high-throughput application, e.g. regional scale assessments. For simpler and faster fractionation via particle size the key issue is the dispersion of the soil. It is unclear, how the initial dispersion of the soil affects the turnover rates of the isolated fractions. In this study, we investigated five commonly used dispersion methods using different intensities (i. e.: shaking in water, shaking in water with glass beads, ultrasonication at 100 J ml-1 and 450 J ml-1 and sodium hexametaphosphate (HMP)). We used soils from field experiments with a change from C3 to C4 vegetation and adjacent control sites using δ13C isotope ratio mass spectrometry. We evaluated the degree of C3/C4 moieties of the fractions, mass and carbon recovery and reproducibility as well as the time expenditures of the dispersions, sieving and drying techniques to develop an efficient and cheap fractionation method. The results indicated that ultrasonication as well as H2O treatment with and without glass beads resulted in fractions with different turnover. Moreover, the isolation performances depended on soil texture. While the isolation of the fractions with water with and without glass beads was equivalent to ultrasonication in soils with low clay contents, these methods had limited potential for soils with high clay contents. Furthermore, treatment with water only had less reproducible results than other tested methods. The SOC recovery was comparable and satisfactory amongst non-chemical dispersion methods and reached over 95 % for each of these methods. The use of sodium hexametaphosphate was unsuccessful due to high time expenditures and strong SOC leaching. We propose particle size fractionation combined with ultrasonic dispersion as a fast and highly reliable method to quantify slow and fast cycling SOC pools for a wide range of soil types and textures.